2012
DOI: 10.1016/j.bbrc.2012.05.035
|View full text |Cite
|
Sign up to set email alerts
|

The enhancer of zeste homolog 2 (EZH2), a potential therapeutic target, is regulated by miR-101 in renal cancer cells

Abstract: We investigated a prognostic significance and the mechanism of aberrant nuclear expression of EZH2, a histone methyltransferase, in human renal cell carcinoma (RCC). We found nuclear EZH2 in 48 of 100 RCCs and it was significantly correlated with worse survival in RCC patients. We detected a decreased expression of miR-101 in 15 of 54 RCCs. We found that re-expression of miR-101 resulted in EZH2 depletion and decreased renal cancer cell proliferation. Our results show nuclear EZH2 as a prognostic marker of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 26 publications
3
31
2
Order By: Relevance
“…9,37,38 The best characterized of these is miR-101. 39 Consistent with the effect of miR-101 in inhibiting EZH2 translation, we observed a profound increase in EZH2 protein in podocytes exposed to an oligonucleotide inhibitor of this miR. Moreover, enhanced EZH2 translation mediated through inhibition of miR-101 was accompanied by an attenuation in both TxnIP expression and ROS accumulation.…”
Section: Discussionsupporting
confidence: 84%
“…9,37,38 The best characterized of these is miR-101. 39 Consistent with the effect of miR-101 in inhibiting EZH2 translation, we observed a profound increase in EZH2 protein in podocytes exposed to an oligonucleotide inhibitor of this miR. Moreover, enhanced EZH2 translation mediated through inhibition of miR-101 was accompanied by an attenuation in both TxnIP expression and ROS accumulation.…”
Section: Discussionsupporting
confidence: 84%
“…P27, a cyclin-dependent kinase inhibitor, has been reported as a target gene of EZH2 in several carcinoma types (15,16). In line with these findings, the present study confirmed that in hepatoblastoma tissues with EZH2 overexpression, p27 expression was downregulated, and that depletion of EZH2 in hepatoblastoma cell lines increased the expression of p27.…”
Section: Discussionsupporting
confidence: 90%
“…interest in basic and clinical studies of cancer. Several studies have demonstrated that EZH2 protein is highly expressed in RCC tissues (33)(34)(35)(36), the level of which is associated with RCC dedifferentiation, suggesting that the EZH2 protein may contribute to RCC progression and metastasis. More recently, studies have indicated that EZH2 protein is highly expressed in prostate cancer tissues, which are also associated with a high rate of metastasis to the bone (16,37,38).…”
Section: Discussionmentioning
confidence: 99%